2015
DOI: 10.1016/j.ccell.2015.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Cell-Autonomous TRAIL-R Signaling Promotes KRAS-Driven Cancer Progression, Invasion, and Metastasis

Abstract: Many cancers harbor oncogenic mutations of KRAS. Effectors mediating cancer progression, invasion, and metastasis in KRAS-mutated cancers are only incompletely understood. Here we identify cancer cell-expressed murine TRAIL-R, whose main function ascribed so far has been the induction of apoptosis as a crucial mediator of KRAS-driven cancer progression, invasion, and metastasis and in vivo Rac-1 activation. Cancer cell-restricted genetic ablation of murine TRAIL-R in autochthonous KRAS-driven models of non-sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
185
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(195 citation statements)
references
References 67 publications
7
185
1
1
Order By: Relevance
“…Here the authors found in vivo that TRAIL-R signaling could promote a variety of effects including invasion, proliferation and migration independently of its apoptotic function but dependent upon PI3K signaling. In line with functional importance, prevention of TRAIL-R signaling (through deletion of TRAIL-R) reduces metastasis while increasing survival in a KRAS-driven mouse model of pancreatic adenocarcinoma 102 . In clinical support, high TRAIL receptor 2 expression correlates with reduced metastasis-free survival in human KRAS-driven cancers 102 .…”
Section: Non-canonical Oncogenic Roles For "Apoptotic" Proteinsmentioning
confidence: 87%
See 2 more Smart Citations
“…Here the authors found in vivo that TRAIL-R signaling could promote a variety of effects including invasion, proliferation and migration independently of its apoptotic function but dependent upon PI3K signaling. In line with functional importance, prevention of TRAIL-R signaling (through deletion of TRAIL-R) reduces metastasis while increasing survival in a KRAS-driven mouse model of pancreatic adenocarcinoma 102 . In clinical support, high TRAIL receptor 2 expression correlates with reduced metastasis-free survival in human KRAS-driven cancers 102 .…”
Section: Non-canonical Oncogenic Roles For "Apoptotic" Proteinsmentioning
confidence: 87%
“…In line with functional importance, prevention of TRAIL-R signaling (through deletion of TRAIL-R) reduces metastasis while increasing survival in a KRAS-driven mouse model of pancreatic adenocarcinoma 102 . In clinical support, high TRAIL receptor 2 expression correlates with reduced metastasis-free survival in human KRAS-driven cancers 102 . In other in vitro settings, TRAIL-R signaling has also been found to stimulate cell migration in a caspase-dependent manner 103 .…”
Section: Non-canonical Oncogenic Roles For "Apoptotic" Proteinsmentioning
confidence: 87%
See 1 more Smart Citation
“…Interestingly, our study found that plumbagin could increase the expression of both DR4 and DR5 in murine xenograft tumors, which was different from the results that only the DR5 expression on the cell surface in vitro. Recently, von Karstedt et al (41) found that high TRAIL-R2 expression correlates with invasion of pancreatic ductal adenocarcinoma into lymph vessels. Upregulation of DR4 not only DR5 might imply more clinical importance and need to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the expression of TRAIL receptors is greatly elevated in many cancer types such as hepatocellular carcinoma, renal carcinoma and ovarian cancer, suggesting that such tumors benefit from the expression of these receptors [25,6]. It is becoming increasingly clear that death receptor engagement, especially in the context of cancer, can lead to outcomes, other than apoptosis, that become subverted by certain tumors to their benefit [23,25,30].…”
mentioning
confidence: 99%